Art After Conceptual Art - Alberro, Alexander; András, Edit; Basbaum, Ricardo; Breitwieser, Sabine; Buchloh, Benjamin H.D.; Buchmann, Sabeth; Crow, Thomas; Draxler, Helmut; Ferrell, Elizabeth; Graw, Isabelle; Molesworth, Helen; Nader, Luiza; et al. (Wien : Generali Foundation Wien MIT Press Cambridge (Massachusetts), 2008)
Ader, Bas Jan ; Armaly, Fareed ; Asher, Michael ; Birnbaum, Dara ; Buren, Daniel ; Chicago, Judy ; Clark, Lygia ; D'Arcangelo, Christopher ; Deleuze, Gilles ; Eichhorn, Maria ; Graham, Dan ; Hart Benton, Thomas ; Huebler, Douglas ; Kelly, Mary ; Kippenberger, Martin ; Klein, Yves ; Kozlowski, Jaroslaw ; Laderman Ukeles, Mierle ; Lawler, Louise ; Leung, Simon ; Little Warsaw ; Loos, Adolf ; Lüpertz, Markus ; Manzoni, Piero ; Margreiter, Dorit ; Norman, Nils ; Piper, Adrian ; Poledna, Mathias ; Rosler, Martha ; Schnabel, Julian ; Williams, Christopher
Engels
boek